Mightier Than the Sword - Archer, Jeffrey (London Pan Books, 2019)
Following the explosion of an IRA bomb on board the Barrington's flagship MV Buckinghorn, Emma Clifton must deal with the repercussions on her family's shipping business. Meanwhile her old adversary, Lady Virginia Fenwick, plots her downfall. Bestselling novelist Harry, Emma's husband, is on a mission to free a fellow author imprisoned in Siberia, even if it costs him everything. Giles, his brother-in-law, a minister of the Crown, faces his own problems when a diplomatic disaster risks his bid for higher office.
Keywords: Clifton, Harry (Fictitious character)